Strategic plan for Helen's Kitchen - Justo, Alvin P. (School of Management, University of the Philippines Mindanao, 2013)
Helen's Kitchen is a food catering services business owned by Mr. Joel Dorado. The company is experiencing a rapid increase of clients but their current serving capacity cannot live up to this increasing demand. This concern has become a great challenge for the catering business and signifies an avenue for potential growth. Hence, a study was conducted to draft a three-year-strategic plan to improve the capacity of Helen's Kitchen and thus, increase its revenue to generate higher profit. The Strategic Conceptual Framework of Fred David was used as a guide in this study. The framework is divided into three parts; strategy formulation, strategy implementation and strategy evaluation. In strategy formulation, the various external factors that affect an organization were analyzed. The political, socio-cultural, economic, technological and environmental issues re tackled to identify the factors that may affect the food catering industry. The intensity of competition in the industry, threats and opportunities were analyzed using Porter's Five Forces Model of Competitive Analysis and measured using External Factor Evaluation (EFE) matrix. Helen's Kitchen got a score of 2.49 which is slightly lower than the 2.5 industry standard. This means that the organization is less responsive to the influence of its external environment. The inherent factors to the organization was likewise analyzed by evaluating sections on human resource, marketing, operations and finance. Internal Factor Evaluation (IFE) matrix was then performed as a quantitative tool to rate the different internal factors. Helen?s Kitchen got an IFE score of 2.43 which implies that the company is internally weak relative to the 2.5 score of the industry standard. The following alternative strategies were formulated using the SWOT Matrix and screened its relative attractiveness using Quantitative Strategic Planning Matrix (QSPM). Results showed the following strategies to be taken are the following: (1) increase in operational capacity, (2) increase in advertising and marketing scheme, and (3) open an eat all you can buffet restaurant. These three were all processed using the QSPM tool and were analyzed according to its attractiveness in addressing the concerns of the business. The increase in operational capacity strategy showed the highest score with 6.36 rate followed by the increase in marketing strategy at 5.6 score and a score of 4.94 for the strategy of opening an eat all you can buffet restaurant. The top two strategies: increase in operational capacity and increase in marketing and advertising efforts were elaborated in the implementation stage. A monitoring schedule and system is also created for the implemented strategies.